PELAKSANAAN PROGRAM MAGANG DUNIA USAHA DAN INDUSTRI DITINJAU DARI PERSEPSI MAHASISWA PROGRAM STUDI PENDIDIKAN ADMINISTRASI PERKANTORAN FKIP UNS TAHUN 2019 - Muhammad Romdoni; Hery Sawiji; Anton Subarno (JIKAP (Jurnal Informasi Dan Komunikasi Administrasi Perkantoran), 2021)
This research aims to figure out: (1) the implementation of business and industrial internship program by the students of Office Administration Education of the year 2019, (2) the strategy implemented by the students of Office Administration Education in convincing partner institutions in the program implementation, and (3) the method used by the students of Office Administration Education to solve the inappropriate competencies on the task given in the implementation of the internship program. This research using qualitative method with narrative approach is applied in this research. Purposive sampling and snowball sampling method are used to select the research subjects and head of office administration education as a key informan The data collection techniques used are interview, observation, and document analysis. The result of the research shows that: 1) the implementation of the internship was in line with the guideline of Office Administration Internship 2017 so that it went smoothly; 2) The strategy implemented by the students in convincing the partner institutions was proposal. The proposals were created as attractive as possible and filled with elaborations of the skills offered by the students; and 3) The students solved the inappropriate competence during the internship period by (1) conducting consultation with the study program, (2) frequently asking questions, (3) asking help from other employees, and (4) studying independently.